CONTENT AND STRUCTURE OF EDUCATIONAL MATERIAL ON PSYCHOLOGICAL COUNSELING: METHODOLOGICAL ASPECTS - Andrey Chernov (Вестник Северо-Кавказского федерального университета)
The article contains a theoretical analysis of educational and methodological publications devoted to the theory and practice ofpsychological counseling, as an academic discipline andfield ofprofessional activity. The study made it possible to identify the logic of the formation of the concept ofvarious aspects ofpsychological counseling, for the subsequent structuring of theoretical and methodological material in the designatedfield of psychological practice. In the methodological aspect, the substantive and procedural components of counseling were singled out, as didactic areas for training and improving the specialist deserved special attention. These components, in turn, are represented by structural units that presuppose a certain sequence of mastering the material and professional development.